Broadband fully automated digitally assisted coaxial bridge for high accuracy impedance ratio measurements. (11th April 2016) - Overney, Frédéric; Lüönd, Felix; Jeanneret, Blaise
Abstract: This paper describes the principle of a new fully automated digitally assisted coaxial bridge having a large bandwidth ranging from 60 Hz to 50 kHz. The performance of the bridge is evaluated making 1 : 1 comparisons between calculable ac resistors. The agreement between the calculated and the measured frequency dependence of the resistors is better than 5 ⋅ 10 − 8 at frequencies up to 5 kHz, better than 1 ⋅ 10 − 7 up to 20 kHz and better than 0.8 ⋅ 10 − 6 up to 50 kHz. This bridge is particularly well suited to investigate the ac transport properties of graphene in the quantum Hall regime.